Revolutionizing Energy Harvesting: Solar Cell Integration with Radio Waves for AI, IT, and Business Applications - George Edison (International Journal of Multidisciplinary Sciences and Arts, 2023)
The dynamic convergence of solar cell technologies, radio waves, information technology (IT), artificial intelligence (AI), and business applications is examined in this study. The combination of these technological components has created a diverse array of innovative opportunities that provide cost-effective, environmentally friendly, and game-changing solutions for a range of businesses. We start by exploring the basic ideas behind solar cells, demonstrating their ability to transform light from the sun into electrical energy, and looking at the various kinds of solar cells and how they work together to gather energy. With uses ranging from off-grid, rural locations to space exploration and residential and commercial installations, solar cells have emerged as key players in the shift to clean, renewable energy sources. Next, we delve into the world of radio waves, which are essential to radar systems, wireless communication, remote sensing, and other fields. We clarify the various uses of radio waves and the difficulties they pose, paving the way for their cooperation with solar cell technology. The combination of radio waves with solar cells opens up new opportunities for business, IT, and artificial intelligence applications. With this connection, off-grid communication networks may be made more sustainable and wireless devices and sensors can be installed in remote or energy-constrained areas. There could be a huge impact on AI-driven applications such as Internet of Things (IoT), smart cities, precision agriculture, and remote data collection. Integration of solar-powered radio wave technology improves sustainability, resilience, and connectedness in the field of information technology. It enables companies to improve supply chain operations, lower energy costs, operate profitably in isolated or disaster-prone places, and support sustainable practices. Among the noteworthy trends influencing the IT sector are edge computing and digital inclusion. We also examine the significant effects of solar-powered radio wave technologies on the business sector. It increases supply chain optimization, energy efficiency, environmental monitoring, and remote monitoring and control. Key themes in this environment include resilience, scalability, and sustainability. Businesses are looking for creative ways to adapt to changing customer demands and legal obligations.